2002
DOI: 10.1139/z02-025
|View full text |Cite
|
Sign up to set email alerts
|

Cougar predation and population growth of sympatric mule deer and white-tailed deer

Abstract: Mule deer (Odocoileus hemionus) populations throughout the west appear to be declining, whereas whitetailed deer (Odocoileus virginianus) populations are increasing. We compared abundance, number of fetuses per female (maternity rate), recruitment, and cause-specific adult (≥1 year old) mortality rate for sympatric mule deer and whitetailed deer in south-central British Columbia to assess population growth for each species. White-tailed deer were three times more abundant (908 ± 152) than mule deer (336 ± 122)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 40 publications
3
86
0
Order By: Relevance
“…If coyotes live in an area with a preferred prey species that is readily available in winter (e.g., snowshoe hares [Lepus americanus]), we would expect coyotes to reduce the time spent hunting ungulates in winter, which should benefit mule deer. As with other forms of alternative prey (Patterson et al 1998;Cooper et al 1999;Ackerman 2002;Prugh 2005;Miller et al 2006), the presence of the second deer species would be likely to influence predation on the first (Robinson et al 2002) and should be considered in future models.…”
Section: V(t)mentioning
confidence: 99%
“…If coyotes live in an area with a preferred prey species that is readily available in winter (e.g., snowshoe hares [Lepus americanus]), we would expect coyotes to reduce the time spent hunting ungulates in winter, which should benefit mule deer. As with other forms of alternative prey (Patterson et al 1998;Cooper et al 1999;Ackerman 2002;Prugh 2005;Miller et al 2006), the presence of the second deer species would be likely to influence predation on the first (Robinson et al 2002) and should be considered in future models.…”
Section: V(t)mentioning
confidence: 99%
“…Times and locales preferred for hunting are clearly relevant to assessing and managing the risks to humans that are increasingly of concern to managers. Under certain circumstances, mountain lion predation can limit bighorn sheep (Ovis canadensis), have potentially deleterious impacts on vulnerable pronghorn (Antilocapra americana), and potentially regulate mule deer (Odocoileus hemionus) and other ungulate populations (Ockenfels 1994, Hayes et al 2000, Logan and Sweanor 2001, Robinson et al 2002, Rominger et al 2004). These direct effects on populations of herbivores potentially translate into indirect effects on vegetation structure and composition (Ripple and Beschta 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Details for obtaining estimates of vital rates from telemetry data are given in Wielgus and Bunnell (1994a and Robinson and Wielgus (2000). Details for estimating population growth from vital rates are given in Wielgus (2002), Wielgus et al (2001), and Robinson et al (2002). Densities of mule deer and white-tailed deer in treatment and control areas will be determined using seasonal and annual aerial surveys.…”
Section: Overall Experimental Approachmentioning
confidence: 99%
“…The Columbia Basin Fish & Wildlife Compensation Program in British Columbia contracted Wielgus to determine if mule deer were declining and the possible cause of the decline if any. Working in the NE IM and adjacent Canadian portions of the Columbia Basin, Robinson et al (2002) found that mule deer populations were decreasing at a finite rate of growth of R = 0.88 (declining at 12%/year) from 1997-2000. During the same time, sympatric white-tailed deer were increasing at R = 1.02.…”
Section: Introductionmentioning
confidence: 99%